Cohomology and its applications on multiplicative Hom-$ δ $-Jordan Lie color triple systems - Lili Ma; Qiang Li (AIMS Mathematics)
The theory of cohomologies on multiplicative Hom-$ δ $-Jordan Lie color triple systems is given. As an application, deformations and extensions on the multiplicative Hom-$ δ $-Jordan Lie color triple system are characterized in view of relevant cohomology.